A complete genetic linkage map and QTL analyses for bast fibre quality traits, yield and yield components in jute (corchorus olitorius l.) - Topdar, N.; Kundu, A.; Sinha, M.K.; Sarkar, D.; Das, M.; Banerjee, S.; Kar, C.S.; Satya, P.; Balyan, H.S.; Mahapatra, B.S. (Цитология и генетика, 2013)
We report the first complete microsatellite genetic map of jute (Corchorus olitorius L.; 2n = 2x = 14) using an F6 recombinant inbred population. Of the 403 microsatellite markers screened, 82 were mapped on the seven linkage groups (LGs) that covered a total genetic distance of 799.9 cM, with an average marker interval of 10.7 cM. LG5 had the longest and LG7 the shortest genetic lengths, whereas LG1 had the maximum and LG7 the minimum number of markers. Segregation distortion of microsatellite loci was high (61 %), with the majority of them (76 %) skewed towards the female parent. Genomewide non-parametric single-marker analysis in combination with multiple quantitative trait loci (QTL)-models (MQM) mapping detected 26 definitive QTLs for bast fibre quality, yield and yield-related traits. These were unevenly distributed on six LGs, as colocalized clusters, at genomic sectors marked by 15 microsatellite loci. LG1 was the QTL-richest map sector, with the densest colocalized clusters of QTLs governing fibre yield, yield-related traits and tensile strength. Expectedly, favorable QTLs were derived from the desirable parents, except for nearly all of those of fibre fineness, which might be due to the creation of new gene combinations. Our results will be a good starting point for further genome analyses in jute. Впервые приводится полная генетическая карта микросателлитов джута (Corchorus olitorius L.; 2n = 2x = 14), полученная с помощью рекомбинантной инбредной популяции F6. Из изученных 403 микросателлитных маркеров 82 были картированы в семи группах сцепления, которые в целом занимают генетическую дистанцию в 799.9 cM со средним интервалом между маркерами 10.7 cM. По генетической дистанции самой длинной была группа сцепления 5, самой короткой группа 7, в то время как максимальное число маркеров имела группа 1, а минимальное – группа 7. Для 61 % микросателлитных локусов наблюдали нарушение расщепления, в 76 % случаев преимущество при передаче имел аллель материнского организма. Геномный непараметрический одномаркерный анализ в комбинации с моделью множественных QTL картировал 26 локусов, отвечающих за качество лубяного волокна, урожайность и признаки, связанные с урожайностью. Они неравномерно распределены в шести группах сцепления как ко-локализованные кластеры в генетических секторах, маркированных 15 микросателлитными локусами. Группа сцепления 1 была сектором, наиболее обогащенным QTL, с плотно расположенными кластерами QTL, отвечающими за выход волокна, и за признаки, связанные с урожайностью и прочностью. Как и ожидалось, в результате возникновения новых комбинаций генов от соответствующих родителей получены сочетания благоприятных локусов, за исключением почти всех локусов, определяющих тонкость волокна. Результаты являются хорошей основой для дальнейшего анализа генома джута. Вперше наводиться повна генетична карта мікросателітів джуту (Corchorus olitorius L.; 2n = 2x = 14), отримана за допомогою рекомбінантної инбредної популяції F6. З 403 вивчених мікросателітних мар-керів 82 були картовані в семи групах зчеплення, які в цілому займають генетичну дистанцію в 799.9 cM із середнім інтервалом між маркерами 10.7 cM. За генетичної дистанції найдовшою була група зчеплення 5, найкоротшою група 7, в той час як максимальне число маркерів мала група 1, а мінімальне – група 7. Для 61 % мікросателітних локусів спостерігали порушення розщеплення, в 76 % випадків перевага при передачі мав алель материнського організму. Геномний непараметричний одномаркерний аналіз в комбінації з моделлю множинних QTL картував 26 локусів, що відповідають за якість луб’яного волокна, врожайність і ознаки, пов’язані з урожайністю. Вони нерівномірно розподілені в шести групах зчеплення як ко-локалізовані кластери в генетичних секторах, маркованих 15 мікросателітними локусами. Група зчеплення 1 була сектором, найбільш збагаченим QTL, з щільно розташованими кластерами QTL, що відповідають за вихід волокна, та за ознаки, пов’язані з врожайністю і міцністю. Як і очікувалося, в результаті виникнення нових комбінацій генів від відповідних батьків були отримані поєднання сприятливих локусів, за винятком майже всіх локусів, що визначають тонкість волокна. Результати є хорошою основою для подальшого аналізу геному джуту.